ASSESSMENT OF HEAVY METAL IMPACT ON TOPSOIL PHYSICOCHEMICAL PROPERTIES IN MGBUKA OBOSI MECHANIC VILLAGE, NIGERIA - Chike Pius Nwachukwu; Chukwuemeka Obumneme Umobi; Louis Chukwuemeka Orakwe; Luke Okwuchukwu Uzoigwe; Victor Obinna Alaribe (Barkah Publishing, 2026)
This study assessed the concentration, distribution, and contamination levels of selected heavy metals in soils from Mgbuka Obosi Mechanic Village, Anambra State, Nigeria, with comparison to a control site at Idemili Farms. Soil samples were collected at depths of 0–30 cm and 30–60 cm and analyzed for heavy metals including cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), and zinc (Zn) using Atomic Absorption Spectrophotometry. Physicochemical properties such as soil pH, moisture content, particle size, bulk density, organic carbon, and nutrient composition were also determined. Results showed higher concentrations of heavy metals in the mechanic village compared to the control site, with the order of abundance as Cu > Fe > Zn > Pb > Cd > Cr. Although most metal concentrations were below permissible limits, contamination factor (CF) and pollution load index (PLI) values indicated moderate contamination, which increased with soil depth. Soil properties revealed slightly acidic conditions, reduced moisture content, and altered nutrient levels in the study area, likely due to continuous anthropogenic activities such as oil spills and metal waste disposal. The enrichment factor (EF) suggested minimal to moderate anthropogenic influence. Overall, the findings highlight potential environmental and health risks associated with prolonged exposure to contaminated soils in mechanic villages. The study recommends immediate intervention and sustainable waste management practices to mitigate further soil degradation and protect surrounding agricultural lands.